A patient with mosaic neurofibromatosis type 2 presenting with early onset meningioma - Chu, Yoyo Wing-Yiu (BMJ Case Rep, 2014)
A female patient was found to have meningioma when she was 3 years and 11 months old and subtotal excision was performed. The residual tumour recurred 3 months after the first excision, and again 11 months after the second one. She was also found to have subcutaneous neurofibroma. However, her clinical features did not fulfil the diagnostic criteria for neurofibromatosis type 2 (NF2), and her family history was unremarkable. Considering that primary meningioma is extremely rare in the paediatric population, the diagnosis of NF2 was considered. It was thought that this might have an impact on her subsequent management. Genetic testing on blood DNA for NF2 was arranged, and the results confirmed that she had mosaic deletion of the promoter to exon 16 of NF2. With uncertainty of whether NF2 mutations are also present in other tissues, vigilant follow-up for other NF2-related complications would be required in the future.